1991
DOI: 10.1346/ccmn.1991.0390504
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Structural Features, and Thermal Behavior of Sodium and Hydrogen Octosilicate

Abstract: Abstract--The chemical composition and the thermal behavior of sodium and hydrogen octosilicate was studied by chemical and thermal analysis, infrared (IR), magic-angle-spinning nuclear magnetic resonance (MAS-NMR) spectroscopy, and X-ray diffractometry. Both compounds are layer silicates with basal spacings of 11.10 and 7.38 ~, respectively. In both forms the ratio of Q4 silicon (connected via oxygen bridges with four silicon atoms) to Q3 silicon (connected with only three other Si atoms) is I. At least a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 10 publications
(15 reference statements)
4
30
0
2
Order By: Relevance
“…This behavior increased the interaction strength between the lamella and hydrated sodium cations and decreased the interlayer spacing. The peaks at higher angles are related to lamellar structure features and also confirm that the ilerite structure was synthesized [4].…”
Section: Ilerite Synthesissupporting
confidence: 68%
See 3 more Smart Citations
“…This behavior increased the interaction strength between the lamella and hydrated sodium cations and decreased the interlayer spacing. The peaks at higher angles are related to lamellar structure features and also confirm that the ilerite structure was synthesized [4].…”
Section: Ilerite Synthesissupporting
confidence: 68%
“…Pure silica samples start their crystallization after 3 days of hydrothermal treatment, as given by very low signals (curve a). After 6 days the ilerite structure is already obtained (curve b), presenting all characteristic diffraction signals [4], however, part of it remains in amorphous phase. Finally, the pure octosilicate structure is obtained after 9 days of reaction (curve c).…”
Section: Ilerite Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…To develop the interlayer microporosity of the chemically modified interlayer, we have reported on alkoxysilylation of ilerite [5] (known as layered octosilicate [6] or RUB-18 [7]) with 4,4'-bis(triethoxysilyl)biphenyl [8,9]. More recently, Mochizuki et al have reported on the silylation of ilerite with 4,4'-bis(trichloro-and dichloromethylsilyl)benzene [10].…”
Section: Introductionmentioning
confidence: 99%